2019
DOI: 10.3390/s19235325
|View full text |Cite
|
Sign up to set email alerts
|

Lower Body Kinematics Monitoring in Running Using Fabric-Based Wearable Sensors and Deep Convolutional Neural Networks

Abstract: Continuous kinematic monitoring of runners is crucial to inform runners of inappropriate running habits. Motion capture systems are the gold standard for gait analysis, but they are spatially limited to laboratories. Recently, wearable sensors have gained attention as an unobtrusive method to analyze performance metrics and the health conditions of runners. In this study, we developed a system capable of estimating joint angles in sagittal, frontal, and transverse planes during running. A prototype with fiber … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 38 publications
(73 reference statements)
0
38
0
Order By: Relevance
“…We utilized a previous approach developed in our group to maximize accuracy with four sensors in specific placements to monitor multiaxes hip kinematics . Each sensor was placed in different orientations (horizontal/vertical/orthogonal, Figure A–C) which allowed the system to learn as many unique relationships between strain of each sensor and hip movement in different planes (sagittal, frontal, and transverse).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We utilized a previous approach developed in our group to maximize accuracy with four sensors in specific placements to monitor multiaxes hip kinematics . Each sensor was placed in different orientations (horizontal/vertical/orthogonal, Figure A–C) which allowed the system to learn as many unique relationships between strain of each sensor and hip movement in different planes (sagittal, frontal, and transverse).…”
Section: Discussionmentioning
confidence: 99%
“…Sensor placement and orientation and the number of sensors can play a major role in improving the accuracy of the multiaxes body motion tracking systems . In this study, sensor locations were used from our previous work that identified optimal sensor orientations for multiaxes hip angle tracking with piezoresistive sensors . The sensors were connected to an LDC1614 chip (see Supporting Information for details, Figure ).…”
Section: Methodsmentioning
confidence: 99%
“…The sensor placement was optimized in a previous study [ 38 ] and four positions were selected by genetic algorithm for a multi-axis hip joint. The positions of the sensors on the knee and ankle were selected according to the joint axes.…”
Section: Methodsmentioning
confidence: 99%
“…To our knowledge, the use of flexible textile (soft) strain sensors for continuous monitoring of fatigue has not yet been studied. Flexible textile strain sensors are a category of wearable sensors that have recently been used for human gait analysis [ 38 , 39 , 40 ], trunk motion monitoring [ 41 , 42 ], and hand gesture recognition [ 43 ]. These sensors work by measuring changes in the resistance or capacitance when they are elongated [ 44 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation